Using a non-surgical transcutaneous intraglandular injection technique to deliver cell and cell-free therapies to murine submandibular salivary glands - Arvind Hariharan; Janaki Iyer; Akram Almansoori; Younan Liu; Meet Shah; Piotr Pater; Tyler Lalonde; Simon D. Tran (PLoS ONE, 2025)
Salivary Glands (SGs) are vital organs that are particularly prone to damage due to head and neck cancer radiation treatment, as well as other autoimmune disorders. SG hypofunction often impairs the production of saliva, which causes a significant loss of functioning for the oral cavity. There are a multitude of treatments for rescuing SG hypofunction; however, they are usually administered systemically, causing adverse effects and requiring higher doses of the agents. More localised approaches have demonstrated adequate potential as alternative treatments but are still in their initial stages of investigation. This study proposes a localised delivery technique termed as the ‘Intraglandular (IG) Non-Surgical Transcutaneous Injection,’ to deliver cell and cell-free therapies into the submandibular salivary glands (SMGs) of mice. First, we used anatomical landmarks, radiography, and tissue dissection to devise a method to localise the center of the SMGs with either a pen marker or a customized plastic stent. Second, we used a dye (trypan blue) to verify the accuracy of the injection technique to the SMGs. Third, we injected Green Fluorescent Protein Bone Marrow Mesenchymal Stem Cells (GFP + ve BM-MSC) and tracked them for 7 days in SMGs to further demonstrate that the cells were embedded into SMG tissue and that our injection technique did not injure the glandular morphology. We therefore hypothesize that this IG technique would provide a less invasive, lower dose and highly accurate administration of cell and cell-free therapies to hypofunctional mice SMGs.